2020
DOI: 10.3390/ijms21020430
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vascular Endothelial Function in Young and Middle-Aged Women with Respect to a History of Pregnancy, Pregnancy-Related Complications, Classical Cardiovascular Risk Factors, and Epigenetics

Abstract: The aim of the study was to examine the effect of previous pregnancies and classical cardiovascular risk factors on vascular endothelial function in a group of 264 young and middle-aged women 3 to 11 years postpartum. We examined microvascular functions by peripheral arterial tonometry and EndoPAT 2000 device with respect to a history of gestational hypertension, preeclampsia, fetal growth restriction, the severity of the disease with regard to the degree of clinical signs and delivery date. Besides, we compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 112 publications
1
34
0
1
Order By: Relevance
“…In the pathomechanism of PE, the primary role of trophoblast invasion disorders in the period of placenta development and placental ischemia has been demonstrated. In addition, increased oxidative stress and inflammation as well as endothelial damage are main elements of the disease pathogenesis [2,[5][6][7]28]. Importantly, different components of tobacco smoke may act on different processes or they may act differently on the same cellular processes, which may cause discrepancies between tests.…”
Section: Discussionmentioning
confidence: 99%
“…In the pathomechanism of PE, the primary role of trophoblast invasion disorders in the period of placenta development and placental ischemia has been demonstrated. In addition, increased oxidative stress and inflammation as well as endothelial damage are main elements of the disease pathogenesis [2,[5][6][7]28]. Importantly, different components of tobacco smoke may act on different processes or they may act differently on the same cellular processes, which may cause discrepancies between tests.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, by searching the Medline database we identified a large scale of microRNAs playing a role in pathogenesis of diabetes mellitus and cardiovascular/cerebrovascular diseases. Finally, we selected for the study a shortlist of 29 microRNAs demonstrated repetitively by numerous scientific teams to be associated with normal stages (development and homeostasis of the cardiovascular system, angiogenesis, and adipogenesis) and pathological conditions and diseases (vascular endothelial dysfunction and inflammation, hypoxia, hypertension and regulation of hypertension-related genes, obesity, dyslipidaemia, atherosclerosis and atherosclerotic plaque formation, insulin resistance, diabetes mellitus and diabetes-related complications, metabolic syndrome, cardiovascular diseases involving the blood vessels (coronary and peripheral artery diseases, carotid artery disease, pulmonary arterial hypertension, cerebrovascular disease, aortic and intracranial aneurysms), cardiovascular diseases involving the heart (congenital heart disease, cardiomyopathies, cardiac dysrhythmias, hypertensive heart disease, myocardial disease, valvular heart disease, inflammatory heart disease, rheumatic heart disease, pulmonary heart disease, and heart failure), chronic kidney disease, ischemia/reperfusion injury, cardiac regeneration and cachexia) ( Table 1 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ,…”
Section: Introductionmentioning
confidence: 99%
“…Women with all ages resulting from physiological structure of bone as well as gradually reducing levels of estrogen and progesterone, which is related with higher rate of bone resorption in osteoclasts are approximately five times possibility to suffer from osteoporosis than men ( Srivastava and Deal, 2002 ; Adler, 2014 ). It was reported that about 200 million women aged between 45 and 55 years are affected by postmenopausal osteoporosis ( Hromadnikova et al, 2020 ). Bone mineral density (BMD) as an essential indicator in clinical practice to appraise osteoporosis is not sensitive to the patients with severe ostealgia and humpback leading to the morbidity rate continues to increase including young adults ( Ha et al, 2020 ; Guo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%